BETWEEN MEDIATOR AMBITIONS AND REAL LEADERSHIP: FRANCE’S ROLE TO SUPPORT UKRAINE IN THE FACE OF GROWING U.S. ISOLATIONISM - Burek, Vasylyna-Myhailyna; Kryvenko, Olesia (Public Management and Policy, 2025)
The paper focuses on a systemic analysis of the trilateral interaction between France, the United States, and Ukraine amid the profound transformation of the international security environment following the full-scale invasion of Ukraine by the Russian Federation in 2022. At the core of the analysis is the evolving nature of Western support for Ukraine, shaped by the strategic reassessment of the United States’ global role and the growing determination of European states to operationalize the concept of strategic autonomy. The study examines the consequences of declining transatlantic cohesion for the redistribution of responsibility in guaranteeing European security, with particular emphasis on France’s increasing activity within both bilateral and multilateral support frameworks for Ukraine. French policy is acquiring a new systemic quality, combining diplomatic engagement, military-technical assistance, and economic cooperation, with a specific focus on joint defense production initiatives and strategic coordination within the EU framework. In parallel, the United States is experiencing rising domestic political polarisation, external policy inconsistency, and a tilt toward isolationism—all of which significantly affect allied strategic behaviour and drive a reconfiguration of responsibilities within the Western coalition. The socio-political dynamics in France reveal a growing public endorsement of support for Ukraine, coupled with a critical perception of the United States’ reliability as a long-term ally. The findings point to the emergence of a new trilateral configuration in which France increasingly assumes a stabilizing role within Europe’s security architecture, while the United States is perceived as a strategically unpredictable actor. For Ukraine, this shift necessitates a strategic recalibration toward diversified formats of partnership, intensified engagement with European actors, and a reconsideration of its foreign policy priorities in response to a dynamically evolving global order.